PODCASTING IN TRANSITION: FORMALIZATION AND ITS DISCONTENTS - Sullivan, John; Aufderheide, Patricia; Bonini, Tiziano; Berry, Richard; Llinares, Dario (AoIR Selected Papers of Internet Research, 2020)
Podcasting has thrived since its popularization in 2004 as a bastion for amateur media production. Over the past ten years, however, entrepreneurs and legacy media companies have rapidly expanded their interests in podcasting, bringing with them professional standards and the logics of capital. Breakout hits such as 2014’s Serial (with nearly 40 million downloads) and This American Life have demonstrated to both programmers and advertisers the potential for podcasting to emerge as a commercially viable media industry (O’Connell, 2015). According to a recent nationwide survey by Edison Research (2019), an estimated 90 million listeners reported having listened to a podcast in the previous month. Despite the medium’s homespun, DIY roots, this dramatic expansion of the podcast audience and interest from legacy media has begun to transform it “from a do-it-yourself, amateur niche medium into a commercial mass medium” (Bonini, 2015, p. 27). This proposed panel aims to explore the transitions currently underway in podcasting. Specifically, each of the papers on this panel address in some way the process of formalization, or the process by which “media systems become progressively more rationalized, consolidated and financially transparent” (Lobato &Thomas, 2015, p. 27). Formalization is not a monolithic process, but rather one that is responsive to existing institutional, regulatory, and cultural structures. It is also historically contingent. The first paper, entitled “Podcasting as a cultural form between old and new media” utilizes a historical lens to link the current trajectory of the medium’s development to the development and domestication of radio in the 1920s as well as the rise of online streaming services in the 21st Century. In particular, this paper situates podcasting in the context of these earlier technologies, arguing that the medium is best understood as a complex interplay between networks of market actors. This complex interplay of actors is explored in more detail by papers 2 and 3. In the second paper, entitled “Formalising the informal: BBC commissions and the shape of podcasts,” the author explores the powerful role of the BBC in providing an institutional and creative framework for podcasting production via its BBC Sounds online radio platform. Through the efforts of this venerable public service broadcaster to reach new audiences by developing podcast content specific to this platform, this paper argues that the medium’s amateur and informal ethos stands to be re-shaped. The third paper, entitled “Protecting public podcasting: Are U.S. news, public affairs, and learning podcasts at risk?”, takes a macro-level view of the formalization process, focusing on podcasts within the U.S. context. Nothing that the most popular podcasts in the U.S. are either learning or information-oriented, this paper argues that the podcast ecosystem fulfills an important public service function. The introduction of platform services like Spotify as power players in podcast distribution, coupled with the rise of advertising as a means of monetization, presents new risks for perpetuation of the medium as an aural public service resource. The fourth paper expands the arguments surrounding podcast formalization by exploring the introduction of market information regimes within the medium. Specifically, this paper explores the development of audience metrics for podcasting, beginning in the mid-2000’s. This paper makes clear that powerful industry players such as Apple and the Interactive Advertising Bureau (IAB) are quickly standardizing the measurement of podcast audiences. These standards create a more transparent market for advertisers, but in so doing they also shift the focus away from the unique nature of podcast content and move it toward notions of audience size. This has the potential to move the medium further away from its amateur roots. Finally, the fifth paper on the panel attempts to reframe the formalization debate by pulling the discussion away from the confining binaries of utopian or dystopian narratives. Instead, this paper situates podcasting within a much broader context by leveraging Don Idhe’s phenomenological philosophy of technology to “speculate on a potential future of reified oral/aural meditation.” This paper considers the nature of the medium itself as a unique “techno-sonic experience”. Here, podcasting is not considered as a medium being shaped by the formalization efforts of institutions or legacy forms of media. Instead, podcasting emerges as a transformational technology that promises a new era of sound integration.